On nonlinear fractional Hahn integrodifference equations via nonlocal fractional Hahn integral boundary conditions - Nichaphat Patanarapeelert; Jiraporn Reunsumrit; Thanin Sitthiwirattham (AIMS Mathematics)
All authors Fractional Hahn differences and fractional Hahn integrals have various applications in fields where discrete fractional calculus plays a significant role, such as in discrete biological modeling and signal processing to handle systems with memory effects. In this study, the existence and uniqueness of solutions for a Riemann-Liouville fractional Hahn integrodifference equation with nonlocal fractional Hahn integral boundary conditions are investigated. To establish these results, we apply the Banach and Schauder fixed-point theorems. Furthermore, the Hyers-Ulam stability of solutions is studied.